2020
DOI: 10.3389/fnins.2020.582079
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Degree Centrality and Functional Connectivity in Parkinson’s Disease Patients With Freezing of Gait: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Objective: Freezing of gait (FOG) is a common disabling motor symptom in Parkinson's disease (PD), but the potential pathogenic mechanisms are still unclear. Methods: A total of 22 patients with PD with FOG (PD-FOG), 28 patients with PD without FOG (PD-nFOG), and 33 healthy controls (HCs) were recruited in this study. Degree centrality (DC)-a graph theory-based measurement of global connectivity at the voxel level by measuring the number of instantaneous functional connections between one region and the rest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 67 publications
5
44
0
Order By: Relevance
“… 22 , 23 Using degree centrality (DC), freezing of gait (FOG) of PD-CN patients has also been correlated with DMN changes indicating the presence of pathological damage. 24 Evidence from ASL research on cognitively normal patients with PD showed that hypoperfusion in the left SMG was negatively correlated with global cognitive performance, consistent with our result. 3 ReHo presumes that the hemodynamic characteristics of each voxel are synchronized with that of every other within a functional cluster, and this synchronization can be altered or adjusted by different conditions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“… 22 , 23 Using degree centrality (DC), freezing of gait (FOG) of PD-CN patients has also been correlated with DMN changes indicating the presence of pathological damage. 24 Evidence from ASL research on cognitively normal patients with PD showed that hypoperfusion in the left SMG was negatively correlated with global cognitive performance, consistent with our result. 3 ReHo presumes that the hemodynamic characteristics of each voxel are synchronized with that of every other within a functional cluster, and this synchronization can be altered or adjusted by different conditions.…”
Section: Discussionsupporting
confidence: 90%
“… 48 Accordingly, the decreased ReHo in the right PCG may be related to an early stage of PD. 13 Hypoactivation in the right PCG of PD patients has been observed in previous RS-fMRI studies, 13 , 17 , 24 whereas the PD-MCI group showed significantly higher ReHo values in the right PCG when compared with the PD-CN group. Overactivation of the sensorimotor cortex has been reported in PD and MCI patients.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations